Adesivos multi-uso-avaliação da resistência adesiva a dentina frente a teste de cisalhamento, estereomicroscopia e microscopia eletrônica de varredura - Gonçalves, Sérgio Eduardo de Paiva [UNESP] (1994)
Recent bonding systems have been advocated as multi-purpose bonding agents. The aim of this study was to determine if some of these bonding systems could be associated to composite resins from different manufacturers. This investigation was conducted to test lhe shear bond strength of three bonding systems: Scotchbond Multi-Purpose (3M Dental Products), Optibond Light Cure (Kerr) and Optibond Dual Cure (Kerr), when each of them was associated to lhe composite resins: Z1 00 (3M Dental Products), Prisma - APH (Dentsply) and Herculite XRV (Kerr). Seventy-two flat dentin bonding sites were prepared to 600 grit on human premolars mounted using acrilic resins. The teeth were assigned at random to 9 groups of 8 samples each. A split die with a 3mm diameter was placed over lhe surface of lhe dentin treated with one of lhe adhesive systems, and lhe selected composite resin was inserted and light cured. The split mold was removed and all samples were termocycled and stored in 37ºC water for 24 hours before testing. Shear bond strength was determined using an lnstron Universal testing machine. Some failures were examined under lhe S.E.M. Data was analysed by one-way analysis of variance, that demonstrated a significant difference (p<0,05) in the mean shear bond strength among Optibond Light Cure (15,446 MPa), Scotchbond Multi-Purpose (13,339 MPa) and Optibond Dual Cure (10,019 MPa). These values did not depend on the composite resin used. The association between bonding system/composite resin was statistycally significant (p<0,05) and the best results were obtained when the composite resins Z100 and Herculite were used with the adhesive system Optibond Light Cure, and when the composite resin APH was used with the adhesive system Scotchbond Multi-Purpose